On Classical Dynamics of Affinely-Rigid Bodies Subject to the Kirchhoff-Love Constraints - Kovalchuk, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
In this article we consider the affinely-rigid body moving in the three-dimensional physical space and subject to the Kirchhoff-Love constraints, i.e., while it deforms homogeneously in the two-dimensional central plane of the body it simultaneously performs one-dimensional oscillations orthogonal to this central plane. For the polar decomposition we obtain the stationary ellipsoids as special solutions of the general, strongly nonlinear equations of motion. It is also shown that these solutions are conceptually different from those obtained earlier for the two-polar (singular value) decomposition.